Preliminary investigation into anthropogenic and natural disturbance effects on the Nile crocodile (Crocodylus niloticus) in the Mutale river, Limpopo province - Gibson, Myfannwyn (My University, 2015)
My study investigated the significance of spatiotemporal heterogeneity on the Nile crocodile (Crocodylus niloticus), a long-lived, apex predator, occupying many African and some South African riverine ecosystems. The scales of study included a long-term investigation of the (indirect) impacts of anthropogenic, landscape scale (100 km2) disturbances on the population demographics of C. niloticus, over 35 years. At the intermediate scale (15 km2), indirect and direct impacts of flooding and seasonality on the health of the C. niloticus population were investigated over a three-year period. This was performed by investigating preferred habitat availability and river quality assessments, including physiochemical variables and rapid bioassessment measures, which served as the ‘smallest’ scale (with samples taken every 500 m). All scales were compared with long-term and short-term investigations into crocodile population demographics. Total crocodile population size within the study river increased over time (from 18 in 1981 to 35 in 2013), but the number of adults decreased (from 9 to 3). Human population size increased at a rate of 3300 individuals per year and anthropogenically altered habitat increased over time from 24% total coverage attributable to farmland on the banks of the Mutale River in 1977, to 66% land coverage in 2013. Increases in humaninduced habitat alterations also created shifts in preferred crocodilian habitat availability. Investigations into the effects of natural disturbances revealed that physiochemistry was seasonally variable, and changed drastically with changes in climate and runoff. The macroinvertebrate communities in the Mutale River differed in time and space for a multitude of reasons, including climate change and changes in habitat. The results of my study showed that Nile crocodiles were affected by alterations to the environment on multiple scales. The study concludes that the long-term population viability of C. niloticus is limited by a combination of these factors.
A dissertation submitted to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. 30 October 2014.
Keywords: Crocodiles.; Crocodiles - Effect of human beings on.; Nature - Effect of human beings on.